INTELLECTUAL CAPITAL IN THE CONTEXT OF MODERN RUSSIAN EDUCATIONAL SPACE: THE ABSTRACT-ANALYTICAL REVIEW OF THE MAIN CONCEPTS AND THEIR INTERPRETATIONS IN THE WORKS OF RUSSIAN SCIENTISTS - T. L. Likhacheva (Модернизация, инновация, развитие, 2016)
In this article the abstract-analytical review of some basic concepts and their interpretations in the writings of native scientists of the last decade. These concepts and their scientific and theoretical treatment is considered by the author in the field of integrative education modernization of modern Russia in the aspect of socio-economic vector of Russian society.